Tattoo and melanocytic nevi. - Milano, A. (European Journal of Pediatric Dermatology, 2019)
In Italy, in the population over the age of 12, approximately 13% of subjects have one or more tattoos, while in America the percentage of tattooed subjects among those aged 18-50 is close to 25% (1). 3.3% of tattooed subjects have side effects, especially related to red color (2). However, tattoos are often used by physicians with considerable advantages both for patients and for the National Health System. Tattoos with a medical purpose, which are included in some essential assistance levels in some countries, can play a key role in the development of tattooing legislation - still absent in Italy and Europe - that can increase tattoo safety with advantages for the tattoo artist and the tattooed subject. Warnings and contraindications to the tattoo (1) must however be respected; in particular, skin areas with nevi must be spared, especially to allow clinical monitoring of the latter.